2022
DOI: 10.3390/ijerph19158918
|View full text |Cite
|
Sign up to set email alerts
|

At Which Area Level Does COVID-19 Infection Matter Most for an Individual’s Self-Rated Health? A Multilevel Fixed-Effects Model Analysis in Japan

Abstract: Several studies have reported the adverse impacts of the COVID-19 pandemic on health outcomes. However, little is known about which area of COVID-19 infection matters most for an individual’s subjective health outcomes. We addressed this issue in the present study. We used the longitudinal data of 2260 individuals obtained from a two-wave internet-based nationwide survey conducted in Japan. We estimated the multilevel regression models, which controlled for fixed effects at the individual and prefecture levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Widespread occurrences of infectious diseases were closely related to symptoms of psychological distress, such as depression and anxiety, which had negative effects on SRH among older people. 12 , 13 Not only the perceived threat but also the actual COVID-19-affectedness played a role with regard to SRH. Studies showed that short- and long-term negative health consequences can result from COVID-19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread occurrences of infectious diseases were closely related to symptoms of psychological distress, such as depression and anxiety, which had negative effects on SRH among older people. 12 , 13 Not only the perceived threat but also the actual COVID-19-affectedness played a role with regard to SRH. Studies showed that short- and long-term negative health consequences can result from COVID-19 infections.…”
Section: Introductionmentioning
confidence: 99%